The Influence of Company Size and Debt to Asset Ratio on Return On Assets - Shahfira, Dwi; Hasanuh, Nanu (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
This research purposed to identify the effect of Company Size (SIZE) and Debt to Asset Ratio (DAR) on Return On Asset (ROA). The dependent variable was Return On Assets (ROA) and the independent variable was Company Size (SIZE) and Debt to Asset Ratio (DAR).  Data were obtained from the financial statement of 12 manufacturing companies in sub-sector of automotive registered on Indonesia Stock Exchange in the period 2014-2018. The study used Multiple Linear Regression Test as the data analysis method. The results show that Company Size partially had a significant positive effect on Return On Assets (ROA). Also, Debt to Asset Ratio (DAR) partially had a significant negative effect on Return On Assets (ROA). Simultaneously, Company Size (SIZE) and Debt to Asset Ratio (DAR) had effect on Return On Assets (ROA). So, the company should keep the stability of the company size and expect to perform debt management properly to optimize increasing the level of Return On Assets (ROA) and remain stable.